Splenogonadal Fusion: A Rare Mimicker of Malignancy - Natalie C. Hartman; Levent Trabzonlu; Güliz A. Barkan; Marcus L. Quek (Case Reports in Surgery)
Splenogonadal fusion is a rare congenital anomaly in which ectopic splenic tissue is found in the testis and can present as a testicular mass mimicking a testicular malignancy. We present a 27-year-old male who presented with a palpable left testis mass suspicious for malignancy and ultimately found to have discontinuous splenogonadal fusion after radical orchiectomy.